The Bidirectional Burden: Renal Dysfunction as a Prognostic Marker in Acute Stroke Patients at BMC Hospital Quetta - Kakar, Amanullah; Qahir, Muhammad; Ihsan ul Haq; Kakar, Ainullah; Ahmed, Riaz; Nasar, Abdul Bari; Essa, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Renal dysfunction is a prevalent comorbidity in acute stroke patients. This study aimed to evaluate the frequency, severity, and prognostic implications of renal impairment in individuals with acute ischemic and hemorrhagic strokes. Methods: This observational, hospital-based cohort study was performed at BMC Hospital Quetta from March 2024 to December 2024, enrolling 140 patients with acute stroke. Renal dysfunction was characterized by an eGFR of less than 60 mL/min/1.73m² or acute kidney injury (AKI) according to KDIGO criteria. Statistical analysis encompassed comparison testing, correlation, and multivariate logistic regression, while controlling for confounding variables. Results: Patients with renal failure (n=56, 40%) were substantially older (68.5±10.2 vs. 62.1±13.5 years; p=0.003) and exhibited elevated rates of hypertension (80.4 vs. 50.0; p=0.01) and diabetes (62.5 vs. 20.2; p=0.02). They demonstrated increased stroke severity (median NIHSS 15 against 10; p=0.001) and higher infarct sizes (32.4±20.1 versus 20.1±15.3 cm³; p=0.004). Renal failure correlated with markedly elevated in-hospital mortality (32.1 vs. 4.8; p=0.001), 30-day mortality (44.6 vs. 10.7; p=0.002), heightened functional disability at discharge (98.2 vs. 37.7; p=0.005), and extended hospital stays (12 vs. 8 days; p=0.003). Multivariate analysis revealed renal dysfunction as an independent predictor of death (adjusted OR: 3.8, 95% CI: 1.9–7.6; p=0.001). Conclusion: Renal failure serves as a critical and independent prognostic indicator for unfavorable outcomes in acute stroke patients, associated with heightened stroke severity, elevated mortality, and increased disability. Timely recognition and customized therapy of renal impairment are essential to enhance outcomes in this at-risk population.